Persistence of metholachlor in sandy clay loam soils under soybean crop - Blanco, Hélio Garcia; Matallo, Marcus B.; Oliveira, Domingos de Azevedo; Blanco, Flávio M. G. (Pesquisa Agropecuaria Brasileira, 2014)
The persistence of the metholachlor herbicide in sandy-clay-loam soils under soybean (Glycine max (L.) Merrill) crop was investigated during three years in three localities of São Paulo state, Brazil. The presence of metholachlor was detected by sorghum bioassay conducted under phytotron conditions for ten weeks after the application. The results showed that metholachlor (1.80 to 3.24 kg/ha of a.i) was not present at phytotoxic levels in the soil samples (0 cm to 10 cm depth) taken from treated plots, two weeks after pre-emergence, for all the three years.